Bagaimana Dampak Jika Pelaku UMKM Menerapkan Laporan Penyusunan Keuangan Berbasis SAK EMKM Terhadap UMKM Desa Tirtosari Kecamatan Banyuasin 1: Studi Kasus Pada Usaha Kerupuk Jangek Maju Lancar - Dewi Eva Nadea; Maryani Ayunda Putri Dyta (AKUNTANSI 45, 2023)
Maju Lancar is a company engaged in the production of Jangek crackers. The company was established in 1985 and is located in Tirtosari Village, Banyuasin 1 District, Banyuasin Regency. Despite the company's decent sales, the financial reporting has not yet adhered to the EMKM Accounting Standards. The aim of this research is to determine whether Maju Lancar SMEs can prepare financial statements based on EMKM Accounting Standards. In this research, the researcher utilized interview techniques, data reduction, data display, and conclusions to obtain data. The research findings indicate that Maju Lancar Jangek Cracker Business has not yet implemented its financial reporting based on EMKM Standards. However, after the researcher provided input to the Micro, Small, and Medium Enterprises (MSMEs) owner, they agreed to adopt EMKM Standards for their business's financial reporting.